The golden autumn2009 - Editorial Article (Овощи России)
On 9th -12th October, the 11th agricultural exhibition the «Golden Autumn» was held All-Russian Exhibition Centre. Agro-forum on «Agro-industrial complex is a base of the crisis management in Russia» was organized in course of the Agro-Exhibition.